Control of bacterial and fungal biofilms by natural products of Ziziphus joazeiro Mart. (Rhamnaceae). (August 2019) - Cosmo Andrade, Jacqueline; da Silva, Ana Raquel Pereira; Audilene Freitas, Maria; de Azevedo Ramos, Bárbara; Sampaio Freitas, Thiago; de Assis G. dos Santos, Franz; Leite-Andrade, Melyna C.; Nunes, Michellângelo; Relison Tintino, Saulo; da Silva, Márcia Vanusa; dos Santos Correia, Maria Tereza; de Lima-Neto, Reginaldo Gonçalves; et al.
Highlights: The EACCZJ presented more effective results against biofilms. The EAFZJ presented significant eradication of mature yeast biofilms. Ziziphus joazeiro aqueous extracts demonstrated a biofilm inhibition effect. Abstract: The aim of this study is to verify the action of the aqueous leaf extract Ziziphus joazeiro in the eradication of bacterial and fungal biofilms, and to compare these effects with the stem bark extracts, as well as with conventional standard drugs. The presence of secondary metabolites was observed through phytochemical prospection assays. The effect of the aqueous extract on microbial biofilm formation was observed by OD600 nm absorbance and the crystal violet assay. For bacterial and fungal biofilms, chlorhexidine gluconate and fluconazole, respectively, were used as positive controls. Phytochemical characterization showed the presence of secondary metabolite classes common to both extracts such as flavonoids, steroids and saponins. In particular, in the aqueous leaf extract phenols, condensed tannins and alkaloids were observed. Eradication results using the aqueous leaf extract showed an inhibition of the microbial biofilm mass, moreover the biofilms were more sensitive to the bark extract, which presented a greater inhibition number and an action similar to standard drugs. It is important to highlight the leaf extract showed significant eradication at the lowest concentrations for mature yeast biofilms, thus demonstrating its potential to modify microbial resistance susceptibility. Bacterial and fungal biofilm eradication results using the Ziziphus joazeiro aqueous extracts presented a biofilm inhibition effect for both, moreover the results support the ethnopharmacological knowledge surrounding the use of Ziziphus joazeiro stems in the community. In comparison, the bark extract presented a more effective treatment than the leaf extract against biofilms, presenting inhibition levels similar to the used standard drugs.